Tingkat Risiko Penyakit Jantung dan Pembuluh Darah pada Dosen dan Karyawan - Sawitri, Harvina; Maulina, Nora; Lutfi, T Yocana; Rahmi, Nita (Jurnal Ilmiah Manusia Dan Kesehatan, 2023)
A lifestyle change will cause a changing pattern of disease at this time. From infection disease and malnutrition becomes degenerative diseases like coronary heart disease. The increased prevalence of coronary heart disease in circle worker and the public in general in Indonesia not only burden the cost of treatment but also lower productivity work and result in more many injury consequence work as well as loss result of work. The purpose of this study is to know the level of risk of coronary heart disease in worker offices (lecturers and employees) at the Faculty of Medicine, Universitas Malikussaleh. The design study uses a cross-sectional study for count factor risk of coronary heart disease in one point time specific to 98 samples. The risk of coronary heart disease is calculated using the Jakarta Cardiovascular Score. Results show that most of the respondents were female (61.2%) and aged 40-44 years (31.6%). Most of the respondents did not suffer from hypertension (normal) as much as 57.1%. Most of the respondents do not suffer from diabetes mellitus (81%), have low physical activity (72.2%), and do not smoke (81%). The level of risk of heart and blood vessel disease is in the low-risk category (58.2%).